Why Automation Needs Error Avoidance Guidelines and Evaluation? - Hussein, Idyawati; Abu Seman, Esmadi Abu; Mahmud, Murni (2010)
Why do we need automation? Many technologies cite three major reasons: to eliminate the dull, the dangerous, and the dirty routines. It is difficult to argue with this answer, but many things are automated for other reasons - to simplify a complex task, to reduce the work force, to entertain - or simply because it can be done. However, none of the above matters relate to the findings of this paper, whereby automation leads to human making mistakes.